ANALISIS SIMULASI EFISIENSI TURBIN ANGIN SUMBU HORIZONTAL AIRFOIL NACA 4415 MENGGUNAKAN BLADE ELEMENT MOMENTUM (BEM) DAN COMPUTATIONAL FLUID DYNAMICS (CFD) - Reva Mazini (2021)
Energy is one of the important factors for socio-economic development. The level of energy consumption by a country often reflects the level of prosperity that can be achieved. Wind is a solution for alternative energy and renewable energy, with the consideration that wind is an unlimited natural resource and is environmentally friendly. The wind turbine used for analysis is a horizontal axis wind turbine. Analysis of the efficiency of this wind turbine used Blade Element Momentum (BEM) and Computational Fluid Dynamics (CFD) simulation methods. The NACA 4415 airfoil is used as the geometric shape of the wind turbine blades, so this airfoil is part of the simulation object to determine the aerodynamic characteristics of the wind turbine blades. With the efficiency of Cp (Coefficient of power) from the results of the two simulations at wind speed variations of 4m/s, 6m/s, 8m/s, 10m/s and 12m/s. At a wind speed of 12 m/s with a rotational speed of 600 rpm, Cp of 0.524 from CFD and 0.523 from BEM was obtained and a power obtained of 1118.47 watts on CFD and 1115 watts from BEM.